2013
DOI: 10.1002/etc.2095
|View full text |Cite
|
Sign up to set email alerts
|

High levels of maternally transferred mercury do not affect reproductive output or embryonic survival of northern watersnakes (Nerodia sipedon)

Abstract: Abstract-Maternal transfer is an important exposure pathway for contaminants because it can directly influence offspring development. Few studies have examined maternal transfer of contaminants, such as mercury (Hg), in snakes, despite their abundance and high trophic position in many ecosystems where Hg is prevalent. The objectives of the present study were to determine if Hg is maternally transferred in northern watersnakes (Nerodia sipedon) and to evaluate the effects of maternal Hg on reproduction. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…However, what little has been reported about the morphological basis for such transport (Conaway & Fleming, ) is not consistent with information on other viviparous snakes (Blackburn, ). Placentation in N. sipedon is of particular interest given ongoing use of this species to monitor maternal‐fetal transfer of environmental contaminants during pregnancy (Bishop & Rouse, ; Chin, Willson, Cristol, Drewett, & Hopkins, ; Cusaac, Kremer, Wright, Henry, Otter, & Bailey, ; Neuman‐Lee, Gaines, Baumgartner, Voorhees, Novak, & Mullin, ). Likewise, information on placentation in Nerodia contributes to a long‐term effort to reconstruct placental evolution in North American thamnophine snakes, a group that has become a model for understanding squamate placentation (Blackburn & Stewart, ; Stewart & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, what little has been reported about the morphological basis for such transport (Conaway & Fleming, ) is not consistent with information on other viviparous snakes (Blackburn, ). Placentation in N. sipedon is of particular interest given ongoing use of this species to monitor maternal‐fetal transfer of environmental contaminants during pregnancy (Bishop & Rouse, ; Chin, Willson, Cristol, Drewett, & Hopkins, ; Cusaac, Kremer, Wright, Henry, Otter, & Bailey, ; Neuman‐Lee, Gaines, Baumgartner, Voorhees, Novak, & Mullin, ). Likewise, information on placentation in Nerodia contributes to a long‐term effort to reconstruct placental evolution in North American thamnophine snakes, a group that has become a model for understanding squamate placentation (Blackburn & Stewart, ; Stewart & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to previous studies that have shown that Hg affects vertebrate immune function (Spalding et al, 2000;Finkelstein et al, 2007;Hawley et al, 2009). However, two recent studies found few adverse sublethal effects of maternally transferred Hg in neonatal N. sipedon (Chin et al, 2013a;Chin et al, 2013b), suggesting that our study species may be more tolerant of Hg than many other species. Future studies that examine species known to experience deleterious effects in response to Hg exposure [e.g.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies on various Nerodia have demonstrated that environmental contaminants can cross the placenta from maternal to fetal tissues during pregnancy (Bishop & Rouse, ; Chin et al, ; Cusaac et al, ). Electron microscopy reveals the chorioallantoic placenta to be a likely route for maternal‐fetal transfer, given its extreme vascularity and the very thin barriers that lie between its uterine and fetal blood vessels…”
Section: Discussionmentioning
confidence: 99%
“…Past research on various Nerodia has shown that whereas most nutrients for development come from the ovulated yolk, placental membranes are responsible for gas exchange as well as maternal‐fetal transfer of organic and inorganic nutrients (Conaway & Fleming, ; Stewart & Castillo, ; Van Dyke & Beaupre, ). Other work has indirectly implicated the placental membranes in maternal‐fetal transfer of environmental contaminants (Bishop & Rouse, ; Chin, Willson, Cristol, Drewett, & Hopkins, ; Cusaac et al, ). Our study tests the hypothesis that fine structure of the placental membranes reflects specific functions, while offering detailed information about placental composition, development, and evolution.…”
Section: Introductionmentioning
confidence: 99%